Pengembangan Instrumen Asesmen Autentik untuk Mengukur Hasil Belajar Siswa dalam Pendampingan Orang Tua pada Masa Pandemi di SD Negeri 01 Krompeng - Wahyu Widiowati; Muhtarom Muhtarom; Sumarno Sumarno (Perkumpulan Kualitama Edukatika Indonesia, 2021)
The government's policy to study from home during the Covid-19 pandemic has made parents more involved in assisting children. This study aims to measure student learning outcomes in mentoring parents during the pandemic. The research was conducted through field studies. Collecting data using questionnaires, interviews, and documents. From the results of the study, it can be concluded that parents have a role as children's learners, fulfilling children's needs, spiritual understanding, supervision, motivation, and providing children's facilities. Children's learning assistance can be seen from the way parents help their child's task difficulties, explain material that children do not understand, and respond well to all online learning from school. Respondents from this study amounted to 164 students. The results of the data analysis showed that the instrument for measuring student learning outcomes in parental assistance during the pandemic was declared reliable and valid with the criteria of